2020
DOI: 10.1002/mgg3.1060
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel protein truncating mutation p.Asp98* in XPC associated with xeroderma pigmentosum in a consanguineous Pakistani family

Abstract: Background: Xeroderma pigmentosum (XP) is a rare genetic disorder, which is characterized by hyper-sensitivity to solar ultraviolet (UV) radiation. Clinical consequences of sun exposure are skin lesions and an increased risk of developing skin cancer. Genetic studies have identified eight genes associated with xeroderma pigmentosum. The proteins encoded by these genes are mainly involved in DNA repair mechanisms. Methods: Molecular genetic characterization of patients with xeroderma pigmentosum involved positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Present study is the third report of XPC mutational analysis from Pakistani population. Previously, Ali et al 1 and Ijaz et al 6 have reported only three mutations (IVS12–1 G>C; p.Gln467*; p.Asp98*) in the XPC gene in families of Pakistani origin.…”
Section: Discussionmentioning
confidence: 95%
“…Present study is the third report of XPC mutational analysis from Pakistani population. Previously, Ali et al 1 and Ijaz et al 6 have reported only three mutations (IVS12–1 G>C; p.Gln467*; p.Asp98*) in the XPC gene in families of Pakistani origin.…”
Section: Discussionmentioning
confidence: 95%
“…According to the Leiden Open Variation Database, over 280 different unique mutations throughout the coding region of FLCN have been identi ed to date. [15] The deletion or insertion of cytosine residues in exon 11 is a recognized mutation hotspot, with nearly half of patients carrying either c.1285delC or c.1285dupC mutations, which are consistent in both European and Asian populations. [2] Other patients have been found to have intragenic deletions or duplications and pathogenic missense mutations.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we presented a novel frameshift variant (c.912delT/p.E305KfsX18) in exon 9 of the FLCN gene, which has not been previously reported in individuals with BHDS. Frameshift mutation may lead to an early termination of protein synthesis or to nonsense-mediated mRNA decay in which the defective mRNA is prematurely degraded ( Ali et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%